Assessment of the gradient jump penalisation in large-eddy simulations of turbulence - Du, Shiyu; Münsch, Manuel; Jansson, Niclas; Schlatter, Philipp (Acta Mechanica, 2026)
This research investigates the efficacy of the gradient jump penalisation (GJP) in large-eddy simulations (LES) when coupled with active subgrid-scale models. GJP is a stabilisation method tailored for the continuous Galerkin spectral element method, aiming at mitigating non-physical oscillations induced by discontinuous velocity gradients across element interfaces. We demonstrate that GJP effectively smoothens fields from LES without a salient impact on flow dynamics for the Taylor–Green vortex (TGV) at Re=1600, periodic hill flows at bulk Reynolds numbers Reb=10,595 and 37,000, as well as turbulent channel flow at Reτ≈550. In the TGV case, the application of GJP results in decreased fluctuations at only high wavenumbers compared to simulations without GJP. The periodic hill flow simulations indicate the applicability of GJP in wall-resolved LES involving curved geometries, though it tends to dissipate some of the finer details in the solution. Finally, in the analysis of the canonical turbulent channel flow cases, GJP leads to a higher resolved turbulent kinetic energy than simulations without GJP and direct numerical simulations. GJP’s mechanism is identified as providing enhanced dissipation at high wavenumbers but accompanied with insufficient dissipation at low wavenumbers, leading to a pronounced spectral cut-off. Non-physical oscillations on element interfaces are reflected as spikes in the power spectral density. By evaluating the sharpness of the strongest spike, GJP is shown to smoothen the spectra, however, without completely removing the gradient jumps at low computational resolution.
CRIS-Team Scopus Importer:2026-01-16